Pengaruh Perceived Ease of Use, Perceived Risk, dan Trust terhadap Minat Menggunakan Aplikasi Pinjaman Online Akulaku pada Masyarakat Daerah Istimewa Yogyakarta - Firlina Dwi Anggraeni; Rasistia Wisandianing Primadineska (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2024)
Akulaku is one of the online loan applications with the most users. In the Special Region of Yogyakarta, the number of online loans in July 2023 increased from the previous month. Based on data from the Financial Services Authority, people aged 19-34 years dominate with the number of active online loan users of 10,688,824 users. The purpose of this study was to determine the effect of Perceived Ease of Use, Perceived Risk and Trust on the interest in using the Akulaku online loan application among the people of the Special Region of Yogyakarta. The data collection method used a questionnaire distributed via the Google Form platform. The sample in this study were people from the Special Region of Yogyakarta who had / currently had the Akulaku application. Sampling was carried out using the Non-Probability Sampling method with a purposive sampling technique. The number of samples was 100 respondents. The data analysis technique used was multiple linear regression and correlation analysis. The results of this study indicate that partially perceived ease of use, perceived risk and trust have a significant positive effect on the interest in using the Akulaku online loan application among people in the Special Region of Yogyakarta.